Deciphering the neural mechanisms of oxytocin’s prosocial and antipsychotic-like effects - Abrahams, Abigail Bethany (2021)
Both clinical and preclinical research has indicated administration of the endogenous neuropeptide oxytocin (OXY) may help restore normal social functioning in patients with social deficits, such as those seen in schizophrenia. In addition, ‘antipsychotic-like’ effects of OXY have also been reported in rats, through the attenuation of phencyclidine (PCP)-induced hyperactivity. OXY has affinity at both the oxytocin (OXTR) and vasopressin 1a (V1aR) receptors, and evidence suggests both are involved in social behaviour. However, the neural mechanisms underpinning these behavioural effects of OXY remain poorly understood. The overall aims of this thesis are to gain an insight into the neural mechanisms that underlie the prosocial and antipsychotic-like effects of subcutaneous (s.c.) OXY in healthy rats, through the use of selective antagonists and intracranial micro-injections of the OXTR targeting toxin, OXY-saporin, into discrete brain nuclei.